1910∼20년대 문명론과 최남선의 『시문독본』소재 문명 관련 논설 분석 - 강미정(Kang, Mijeong) (人文學硏究, 42(0), 2024)
이 글은 1910∼20년대 문명론과 독서에 대한 관심을 개괄하고, 시문독본에 수록된 문명 관련 논설에 담긴 문명리터러시로서의 의미를 분석한 것이다. 이 글에서 말하는 ‘문명리터러시’는 담론과 이데올로기보다는 읽기를 통하여 습득하게 되는 문명의 개념, 현상, 특징 등을 수용하고 활용하는 능력을 가리킨다. 2장에서는 1910∼20년대 문명론과 독서에대한 관심을 다루었다. 그에 따라 1920년대 문명론의 경우, 그 이전에 강세였던 서구 중심문명우위론 보다는 민족갱생과 개인의 성장 및 발전 등에 중점을 두며, 조선학을 위한 관심과 노력, 독서 장려 등으로 확장되었다고 파악하였다. 3장에서는 시문독본이 문명리터러시를 실천하는 자료라는 상정하에 시문독본에 소재한 문명 관련 논설을 살펴보고, 그의미를 탐색하였다. 그에 따라 시문독본에 실린 문명 관련 논설을 첫째, 사회 구성원의협조와 공생, 둘째, 시간과 약속 엄수, 셋째, 부의 실용적 분배와 효율성 등으로 분류하고그 내용을 분석하였다. 이를 통하여 시문독본소재한 문명 관련 논설에는 문명화를 위한 요인으로 사회화, 시간엄수(특히 타인과의 관계속에서), 공공의 이익 등이 제시되었음을알 수 있었다. This article aims to analyze the search for civilization literacy in the 1920s, focusing on the civilization-related editorials contained in Simundokbon (The Anthology of Contemporary Writing). In an era when the thesis of civilization, which combines enlightenment and the will to save the country, was emphasized, Choi Nam-seon’s Simundokbon can be said to be a reading material that had an extraordinary understanding of civilization in that it emphasized individual efforts and the direction of development. Therefore, it was necessary to clarify the purpose more explicitly, focusing on the content most aligned with the purpose of civilization among the editorials. Accordingly, Chapter 2 outlines the theory of civilization and the interest in reading in the 1910s and 1920s. Chapter 3 explores the meaning of civilization literacy, focusing on content close to the purpose of civilization among the editorials included in Simundokbon. The theory of civilization in the 1920s focused on individual knowledge acquisition at a certain distance from the theory of the supremacy of civilization centered on the West, which was strong before that. It was found that the desire for knowledge led to the encouragement of reading. KCI Citation Count: 0